Planteamiento de un modelo matemático para la evaluación de acuíferos de aguas termales: caso de estudio sistema geotérmico de Paipa (2020)
Documentary study thesis for the technical evaluation of the exploitation of underground geothermal aquifers using mathematical models presents state of the art regarding the tourism and therapeutic industry that gives rise to the exploitation of this resource. The case study of the geothermal system that feeds the tourism industry of Paipa in the department of Boyacá - Colombia is presented.